Eco-Friendly Synthesis of Silver Nanoparticles Using Aqueous Extract of Ziziphus Spina-Christi Seeds: Characterization and Stability - Faraj, Mansour; Faraj, Abudelrhman; Erhayem, Mohamed (Journal of Pure & Applied Sciences, 2023)
In this study, silver nanoparticles (Ag-NPs) were prepared using an aqueous extract of Ziziphus Spina-Christi Seeds (ZSCS) powder as an eco-friendly material, reducing agent and capping ligand. The synthesized Ag-NP was characterized using UV-visible absorption spectroscopy (UV-Vis), Fourier transform infrared (FTIR), transmission electron microscopy (TEM) and dynamic light scattering (DLS). From The UV-Vis spectra, the surface plasmon resonance (SPR) absorption band at 443 nm confirmed the formation of Ag-NPs. The TEM results demonstrated that the synthesized Ag-NPs have mostly spherical shapes with a particle size of 21.54 nm. In addition, the particle size and the specific surface area (SSA) of Ag-NPs decreased with increasing ZSCS powder extract volume and AgNO3 concentration. The basic medium was found to be better than the acidic medium to prepare Ag-NPs. At a pH value equal to 9.5, within 30 minutes, the color of the solution was changed from colorless to brownish-orange. SPR absorption band of Ag-NPs demonstrated that the synthesized Ag-NPs have high stability over a period of 8 months.  From FTIR results, the stretching of C-O group at 1223 and 1031 cm-1 disappeared after bioreduction of AgNO3, these results may be due to that Ag reduction was carried out by some hydroxyl groups that get oxidized at the expense of Ag+ because Ag+ is reduced to Ag-NPs.